Achieving Efficient Ternary Organic Solar Cells Using Structurally Similar Non‐Fullerene Acceptors with Varying Flanking Side Chains. Issue 14 (24th February 2021) - Chang, Yuan; Zhang, Jianquan; Chen, Yuzhong; Chai, Gaoda; Xu, Xiaopeng; Yu, Liyang; Ma, Ruijie; Yu, Han; Liu, Tao; Liu, Pei; Peng, Qiang; Yan, He
Abstract: In this work, the properties and performance of three structurally similar non‐fullerene acceptors (named BTP‐Ph, BTP‐Th, and BTP‐C11) possessing different side chains on the β‐positions of the thienothiophene units of the Y6 molecule are systematically studied. The steric and electronic effects of these side chains on the blend morphology and device performance based on the PTQ10 donor polymer are investigated. It is found that the thiophene and benzene units on the side chains introduce more steric hindrance and thus slightly reduce the crystallinity of the molecule. However, an interesting matching trend with the PTQ10 donor that appears to better match with the less crystalline molecules is observed. Overall, PTQ10:BTP‐Ph delivers the highest performance of 17.1% due to the suitable phase separation among three blends. Next, a ternary strategy is explored by incorporating BTP‐Th/BTP‐C11 with better molecular packing into PTQ10:BTP‐Ph, which successfully extends photon response, enhances charge transport, and suppresses charge recombination compared with the binary blend. Due to these synergistic effects, the ternary device based on PTQ10:BTP‐Ph:BTP‐Th achieves an outstanding power conversion efficiency of 17.6% with a fill factor of 78.8%, which is the highest value of PTQ10‐based devices to date. Abstract : Three structurally similar non‐fullerene acceptors with various outer side chains are designed and matched with a cost‐effective donor polymer named PTQ10 to fabricate organic solar cells. High efficiencies of 17.1% and 17.6% are achieved by the PTQ10‐based binary and ternary devices, respectively, demonstrating the significance of material compatibility in fine‐tuning morphology toward high‐performance organic photovoltaics.